ENHANCEMENT OF ACTIVATED CARBON FROM LEUCAENA BY HYDROTHERMAL CARBONIZATION TECHNIQUE FOR DYE ADSORPTION IN WASTEWATER - Yoyrurob, Sucheewan; Charnnok , Boonya; Boonsai, Palakorn (Life Sciences and Environment Journal, 2025)
Batik fabric production often results in the loss of dyes during the dyeing process, leading to the release of dye-contaminated wastewater into the environment, which affects the ecosystem. Activated carbon is recognized as a low-cost, environmentally friendly adsorbent with strong potential for wastewater treatment. This study aims to determine the optimal conditions for hydrochar production via hydrothermal carbonization (HTC) at temperatures ranging from 200 to 260°C and contact times of 30 to 120 min, and to investigate the optimal conditions for dye adsorption from wastewater using activated carbon derived from the hydrochar. The results indicated that the optimal condition was achieved at 220°C for 120 min, producing activated carbon with the highest iodine number (1,383.6 ± 25.9 mg/g) and the largest specific surface area (1,555.5 m²/g). SEM and BET analyses confirmed a porous structure favorable for adsorption. Maximum dye adsorption occurred at pH 3, while dye concentrations above 300 mg/L resulted in a decreasing adsorption trend. Adsorption equilibrium was reached within 90 min. The adsorption process followed the pseudo-first-order kinetic model and Langmuir isotherm, indicating a physical monolayer adsorption mechanism, with a maximum adsorption capacity of 116.3 mg/g. HTC at temperatures not exceeding 220°C for 120 min is recommended to optimize yield and preserve pore structure. This study demonstrates a sustainable approach to adding value to local waste materials for effective environmental management.